(untitled) (Revista Ciência Agronômica, 2021)
The maturation stage of seeds affects their physiological quality soon after harvest. The aim of this study was to evaluate the anatomical, histochemical, and physiological changes in chickpea ‘BRS Aleppo’ seeds obtained from pods in different maturity stages. Pods were collected in fi ve maturity stages: green, yellow-green, yellow, golden-yellow, and brown. For anatomical and histochemical characterization, sections were stained with toluidine blue, Lugol’s solution, Xylidine-Ponceau (XP), and ruthenium red. For evaluation of physiological changes, seeds were dried to 12% (wet basis) water content. The following tests were performed: seed water content, germination, percentage and speed of seedling emergence, and electrical conductivity. A completely randomized experimental design was used, with four replications. As the chickpea seeds develop, the innermost layers of the seed coat collapse. Accumulation of starch and protein were already observed in the seeds of green pods and pectin was prominent compound of the seed coat sclerids. In general, chickpea seeds from yellow, golden-yellow and brown pods have greater germination and vigor.